Perkembangan Kerajinan Anyaman Pandan Kampung Aro Balah Aie Nagari Koto Tinggi Kecamatan Enam Lingkung Kabupaten Padang Pariaman 2009-2023 (Studi Kasus: Usaha Anyaman Pandan Ani Anyaman) - Agneshia, Lidia; Najmi, Najmi (Jurusan Sejarah FIS UNP, 2024)
The research discusses the development of Pandan Woven Crafts in Aro Balah Village, Aie Nagari Koto Tinggi, Enam Lingkung District, Padang Pariaman Regency 2009-2023 (Case Study of Ani Anyaman). The aim of this research is to look at the development of pandan weaving in Aro Balah Aie Nagari Koto Tinggi Village, Enam Lingkung District, Padang Pariaman Regency in 2009-2023 (case study of Ani woven) and see the impact of the development of Ani woven on the economy of the community around Kampung Aro. This research uses a historical method which consists of four stages, namely heuristics, source criticism, interpretation, and historiography. The primary sources used in this research are documents in the form of photographs (archives) regarding the pandan woven crafts of Kampung Aro, letters, and so on. These data were obtained from an archival study conducted in the private home of one of the woven business owners, namely Ani woven. Meanwhile, secondary sources were obtained through interviews with the owner of the Ani woven business, namely Mrs. Arni Yulis and the people who work at the Ani woven business. The results of the research obtained are that the Ani Woven business from its founding in 2009 to 2023 has experienced many business name changes and business ups and downs. Ani woven has also opened up new job opportunities for the people of Kampung Aro where previously the people only worked as rice farmers, then after the introduction of Ani woven, many people worked as weavers.